Effect of Yoga Therapy in Elderlies with Hypertension Through Mobile App - Supparang Ruangvanich; Manop Phoosuwan (Scientific Research, New Technologies and Applications Vol. 5, 2024)
The objective of this study is to assess the effectiveness and ease of use of this mobile application in the particular setting of yoga therapy for older individuals with hypertension. Unmanaged hypertension can lead to the development of other health complications, such as cardiovascular disease, stroke, and kidney disease. The research methodology utilizes a quasi-experimental approach and includes experiment groups, control groups, pre-test groups, and post-test groups. The trial was conducted at the Nawamin 9 Hospital in Minburi, with surgeries slated to begin in December 2022 and end in November 2023. The study entailed conducting an extensive interview with a total of 243 patients, which included 10 professionals specialized in mobile application development and 10 experts in yoga. A survey was conducted to gather 400 samples in order to assess the demand for mobile applications. The random sampling method was used to acquire the samples. Initially, it was noted that the pre-test and post-test evaluation outcomes for the usage of the mobile application showed a decrease in hypertension levels in both the control and experimental groups. The smartphone application features instructional materials on hypertension as well as meditation exercises. This research provides suggestions for managing hypertension during illness, promoting self-care, reducing sodium intake, implementing non-pharmacological strategies to lower hypertension, establishing guidelines for hypertension reduction, and incorporating specific yoga activities for hypertension reduction. A total of 50 persons with hypertension received highly effective training with the mobile application, which exhibited outstanding quality. Furthermore, it was found that the overall level of contentment was heightened.